Indigenist mobilization :confronting electoral communism and precarious livelihoods in post-reform Kerala - Steur, Luisa (Dislocations, 2017)
In Kerala, political activists with a background in Communism are now instead asserting political demands on the basis of indigenous identity. Why did a notion of indigenous belonging come to replace the discourse of class in subaltern struggles? Indigenist Mobilization answers this question through a detailed ethnographic study of the dynamics between the Communist party and indigenist activists, and the subtle ways in which global capitalist restructuring leads to a resonance of indigenist visions in the changing everyday working lives of subaltern groups in Kerala.